Tripeptide-based macroporous hydrogel improves the osteogenic microenvironment of stem cells. Issue 30 (19th July 2021) - Li, Qian; Zhang, He; Pan, Jijia; Teng, Binhong; Zeng, Ziqian; Chen, Yang; Hei, Yu; Zhang, Siqi; Wei, Shicheng; Sun, Yuhua
Abstract : A tripeptide-based macroporous hydrogel simultaneously promoted osteogenesis and angiogenesis, which is significant for 3D cultures and stem cell-based tissue engineering. Abstract : Due to the ability to combine multiple osteogenic induction "cues" at the same time, hydrogels are widely used in the three-dimensional (3D) culture of human mesenchymal stem cells (hMSCs) and osteoinduction. However, the survival and proliferation of stem cells in a 3D culture system are limited, which reduces their osteogenic differentiation efficiency. In addition, the cells inside the hydrogel are prone to apoptosis due to hypoxia, which is a serious challenge for tissue engineering based on stem cells. In this study, a tripeptide-based macroporous alginate hydrogel was prepared to improve the osteogenic microenvironment of stem cells. The arginine–glycine–aspartate (RGD) peptide promoted the adhesion and proliferation of stem cells, and the degradation of gelatin microspheres (GMs) produced a macroporous structure to enhance further the migration and aggregation of stem cells. Mesoporous silica nanoparticles (MSNs) sustained-release bone-forming peptide-1 (BFP-1) induced osteogenic differentiation, and the sustained release of the QK peptide from the GMs promoted angiogenesis. In vitro experiments have shown that this functionalized hydrogel stimulates the proliferation of hMSCs, encourages larger cell cluster formation, and enhances the osteogenic differentiation efficiency. The released QK facilitates the proliferation and migration of endothelial cells. In vivo experiments have also verified that this system has a better osteogenic effect, and more blood vessels were observed inside the hydrogel, than in other systems. In general, this research has led to the development of a tripeptide macroporous hydrogel that can simultaneously promote osteogenesis and angiogenesis, showing great promise for applications of 3D cultures and stem cell-based tissue engineering.